The Effectiveness of Group Guidance with ‘Cope with the Feeling of Being Overwhelmed’ Technique on Students’ Assertiveness: A Quasi-Experimental Study - Siti Nurhaliza; Ahmad Syarqawi (Yayasan Sembilan Pemuda Indonesia, 2026)
This study aims to evaluate the effectiveness of group counseling utilizing the “Cope with the Feeling of Being Overwhelmed” technique in improving student engagement at SMP Muhammadiyah 57 Medan. Employing an experimental pretest-posttest control group design, the research divided subjects into an experimental group receiving the counseling intervention and a control group that did not. Data were collected using a validated and reliable student engagement questionnaire and analyzed statistically. The results demonstrated a significant increase in engagement within the experimental group, with a pretest-posttest significance value of 0.000. Furthermore, a significant difference (p=0.007) was found between the experimental and control groups, confirming the intervention’s efficacy. The novelty of this research lies in applying and empirically validating this specific therapeutic technique within a school counseling context to directly target engagement. A key practical implication is that school counselors can adopt this structured group counseling technique as a proven, alternative strategy to actively help students manage overwhelming feelings and thereby foster higher academic participation. This study contributes by providing empirical evidence for a practical counseling method and offering a replicable framework for enhancing student engagement through targeted emotional coping strategies in educational settings.